PENGEMBANGAN MEDIA BERBASIS KOMPUTER DENGAN LECTORA INSPIRE UNTUK MENINGKATKAN PEMAHAMAN SISWA TENTANG PENGAMALAN NILAI-NILAI PANCASILA DI KELAS III SEKOLAH DASAR - Musafa, Ali (Universitas Negeri Surabaya, 2018)
ABSTRACTThe study of learning media development is motivated by the lack of availability of computer-based learning media PPKn in elementary school. The type of research used is research and development using 4-D development model, by executing various stages of development covering the stage of defining, designing, developing and disseminating. The subjects of this media development research are grade III-A students as experimental grade and III-B as control class at SDN Pakis I / 368 Surabaya. Based on the results of assessment of media experts and material experts on computer-based learning media obtained value with the category of